Muslims, fundamentalists, and the fear of the dangerous other in American culture - Watt, David Harrington (The journal of religion & society, 2010)
Beginning in 1979, people living in the United States began using a term, "Islamic fundamentalism," which had not previously been a part of their standard vocabulary. This article examines the controversies produced by the creation of this category and uses those controversies as a springboard from which to reflect on the ways people who live in the United States think about Islam, religion, and "fanatical" beliefs and practices.